Evaluation of serum electrolyte values of Philippine Sheep raised at a semi-intensive farm in Los Banos, Laguna - Prado, Ian Cary B.; Tumamac, Gabriel L.; Constante, Jesalyn L. (2021)
The study was conducted to evaluate serum electrolyte values (total Ca, P, Na, K, Na/K ratio, Cl, Mg, and TCO2) of Philippine sheep and determine their relationship with age and sex. Serum samples of 44 apparently healthy Philippine sheep were examined using a biochemistry analyzer. Mean, standard deviation, and p values were computed for the different parameters and compared with the reference values. Results showed that the serum Na, K, P levels were significantly higher in sheep that are ≤ 1 year old than sheep that are > 1 year old (p<0.05). On the other hand, sheep that are > 1 year old had significantly higher TCO2 than sheep that are ≤ 1 year old (p<0.05). Male sheep had significantly higher total Ca values than female sheep whereas female sheep had significantly higher P levels than male sheep (p<0.05). Serum K and P values were negatively correlated with age (p<0.05). Male sheep had significantly higher total Ca values than female sheep (p<0.05). The data obtained from the study are considered as the first reported values for serum electrolytes of Philippine sheep which can be used to develop reference values.
Keywords: Small ruminants; Sheep; Electrolytes